Does wetland restoration create an ecological trap for migrating Brown trout smolts? - Sortland, Lene K.; Birnie‐Gauvin, Kim; Lennox, Robert J.; Flávio, Hugo; Koed, Anders; Aarestrup, Kim (Restoration ecology, 2025)
Restoring wetlands is often used by management to boost ecosystem services like improving downstream water quality, but it may create ecological traps for migrating salmonids by increasing migration time and predation rates, potentially compromising self‐sustaining populations. In River Gudenaa, Denmark, the wild Brown trout (Salmo trutta) population has declined over the past one to two decades, and it remains unclear whether this decrease is linked to higher mortality due to restored wetlands in the river's lower reaches. This study investigated the progression rates and survival of migrating wild Brown trout smolts through River Gudenaa and Randers Fjord before and after the wetland restoration using acoustic telemetry. In 2020 and 2021, 150 smolts were tagged and released, and their movements and survival were compared with those of 61 smolts tagged and released before the restoration, in 2003 and 2005. Smolt progression rates were significantly slower in the river and fjord after the restoration, with the greatest reduction in the river. Despite slower progression rates, restoration did not impact survival, suggesting the wetlands did not act as an ecological trap for smolts. However, it remains unknown whether the slower migration had carryover effects on sea survival by increasing energy expenditure and delaying sea arrival. The retention of a main river channel, with a directed albeit slower flow, likely kept smolts from venturing into the adjacent wetland lakes, where predation may be higher. By incorporating measures that support migrating fish, wetland restoration can remain a valuable management tool to secure ecosystem services while sustaining fish populations.